2011
DOI: 10.1002/chir.21035
|View full text |Cite
|
Sign up to set email alerts
|

Absolute stereochemistry of altersolanol a and alterporriols

Abstract: The absolute stereochemistry of altersolanol A (1) was established by observing a positive exciton couplet in the circular dichroism (CD) spectrum of the C3,C4-O-bis(2-naphthoyl) derivative 10 and by chemical correlations with known compound 8. Before the discussion, the relative stereochemistry of 1 was confirmed by X-ray crystallographic analysis. The shielding effect at C7'-OMe group by C1-O-benzoylation established the relative stereochemical relationship between the C8-C8' axial bonding and the C1-C4/C1'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…The profile for the theoretical spectrum thus obtained showed good agreement with the experimental spectrum of 1, affirming the foregoing discussions. 10,11) The molecular formula of 2 was determined to be C 13 H 16 O 6 based on the ESI mass spectrum (m=z 269.1023 ½M þ H þ calcd. 269.1025).…”
Section: Resultsmentioning
confidence: 99%
“…The profile for the theoretical spectrum thus obtained showed good agreement with the experimental spectrum of 1, affirming the foregoing discussions. 10,11) The molecular formula of 2 was determined to be C 13 H 16 O 6 based on the ESI mass spectrum (m=z 269.1023 ½M þ H þ calcd. 269.1025).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the CD spectra ( Figure 6) with that of the the known compound alterporriol N, because the CD spectra were less sensitive to the configuration of the four chiral centres [10,16], according to the trends of CD between compound 3 and alternporriol N, we suggest that the absolute configuration of the chirality axis for compound 3 can be assigned as aS.…”
Section: Resultsmentioning
confidence: 93%
“…Anthraquinones and tetrahydroanthraquinones are widely distributed as secondary metabolites in natural biosources, and show important biological activities [2][3][4][5]. So far, 18 compounds of alterporriol family [6][7][8][9][10][11][12] and 14 compounds of altersolanol family [9,[13][14][15][16] have been reported. Herein, we report that the isolation, elucidation and biological activities of the anthraquinone and tetrahydroanthraquinone derivatives from Alternaria sp.…”
Section: Introductionmentioning
confidence: 99%
“…Two endophytic strains of S. globuliferum also produced alterporriols H and K, altersolanol L, stemphypyrone [43], alterporriols D and E, altersolanol A, altersolanols B and C, and macrosporin [44], while an another endophytic strain of S. botryosum produced altersolanol A, curvularin, dehydrocurvularin, macrosporin, and stemphyperylenol [45]. A strain of S. herbarum produced alterporriols D-G and altersolanol A [46]. Recently, it has also been shown that Stemphylium metabolites have biological activities, such as cytotoxic and antibacterial effects [43,44] that may be of interest to the pharmaceutical industry.…”
Section: Secondary Metabolites and Pathogenicitymentioning
confidence: 99%